Penggunaan Textpuzzle dalam Kemampuan Membaca Bahasa Jerman - Widya, Arhamna Danur; Anwar, Muhammad; Asri, Wahyu Kurniati (Universitas Negeri Makassar, 2024)
Abstract. This research is a Quasi-Experiment which aims to obtain data and information about the effectiveness of the use of Textpuzzle game in German text reading ability of XI grade students of SMA Negeri 14 Makassar. The population of this study were all students of class XI IPS SMA Negeri 14 Makassar which amounted to 60 students from two classes. The samples in this study were selected using random sampling technique with a total of 30 samples for the experimental class, namely class XI IPS 3, and 30 samples for the control class, namely XI IPS 4. The data in this study were obtained from the reading ability test results and analyzed using paired t-test (2-tailed). The results of data analysis showed that the average value of students' reading ability in the experimental class before being taught using the Textpuzzle game was 30.83. The value also shows that students' reading ability has not reached the minimum passing score of 75. After being taught using the Textpuzzle game, the average value of students experienced a significant change to 81.23. The result of the t-test analysis showed that the significance value was 0.000 <0.05. Based on this comparison, it can be concluded that the use of Textpuzzle game is effective in German reading abilityKeywords: Game, Textpuzzle, German, Reading Abilitys